Porous materials for removing impurities from raw materials
By using porous materials containing α-alumina and selected metals as protective beds, insufficient phosphorus trapping and coking problems in the hydrotreatment system are solved, and more efficient impurity removal and system stability are achieved.
Patent Information
- Application Number
- CN202180046007.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-07
- Filing Date
- 2021-07-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-07-06
AI Technical Summary
When handling renewable raw materials, existing hydrotreatment systems are difficult to effectively remove impurities such as phosphorus, resulting in rapid passivation of the catalyst and shortening of cycle time, and conventional protective bed materials are prone to coking due to excessive metal content.
Porous materials containing α-alumina and selected metals (such as Co, Mo, Ni, W) are used as protective beds to improve the capture capacity of phosphorus through their high pore volume and appropriate pore size distribution, and control the metal content to reduce coking.
It significantly improves the ability to capture phosphorus, extends the life of the catalyst, and reduces coking, ensuring the stable operation of the hydrotreatment system.
Smart Images

Figure CN115734997B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a porous material containing aluminum oxide, in particular to a porous material for removing impurities from a raw material. The porous material comprises aluminum oxide, and the aluminum oxide comprises alpha aluminum oxide and optionally theta aluminum oxide. The porous material further comprises at least one metal selected from Co, Mo, Ni, W and a combination thereof, and has a molecular weight of 1-110 m 2 The porous material has a total pore volume of 0.50-0.80 ml / g, such as 0.50-0.75 ml / g, or 0.55-0.70 ml / g, or 0.60-0.70 ml / g (as measured by mercury intrusion), and a pore size distribution (PSD), wherein at least 30 vol%, such as at least 40 vol%, at least 50 vol%, or at least 60 vol% of the total pore volume is a radius ≥ (40nm) pores, suitably with a radius ≥ (50 nm) pores, e.g., with a radius of at most The present invention also relates to a method for removing one or more impurities, such as phosphorus (P), from a raw material containing impurities, such as a renewable feed, by contacting the raw material with a guard bed comprising the above-mentioned porous material. The present invention also relates to a guard bed comprising a porous material for a hydroprocessing system, a hydroprocessing system comprising a guard bed comprising a porous material and a downstream hydroprocessing section (hydroprocessing stage) comprising at least one hydroprocessing catalyst, and also to the use of the porous material as a phosphorus protectant in a hydroprocessing method. The present invention also relates to the porous material, but not including metals, and its use as a phosphorus protectant in a hydroprocessing method. Background Art
[0002] Renewable fuels can be produced from a variety of sources, including animal fats and vegetable oils, but also tall oil, pyrolysis oils, and other non-food compounds. Before feedstocks derived from renewable organic materials can be used in conventional automobile engines, aircraft turbines, marine engines, or other engines, and distributed using existing fuel infrastructure, it is desirable to convert the materials into hydrocarbons similar to those found in petroleum-derived transportation fuels. To this end, a well-established approach is to convert vegetable oils into normal paraffins in the gasoline, jet fuel, or diesel boiling range using a hydroprocessing process.
[0003] In the hydroprocessing process, renewable organic materials are reacted with hydrogen in a catalytic reactor at high temperature and pressure.
[0004] A particular problem with feedstocks such as renewable feedstocks is that they contain impurities such as phosphorus- or silicon-containing substances. Phosphorus-containing substances may be present in the form of phospholipids, such as lecithin extracted from seed oils. Waste lubricating oils may also contain substances such as zinc dialkyl dithiophosphates (ZDDP), which act as anti-wear additives in such lubricants. Phosphorus (P) quickly deactivates traditional catalysts used for hydroprocessing and significantly reduces cycle times. Refiners processing renewable feedstocks are forced to load more materials to protect hydroprocessing catalysts compared to fossil fuel-based refining processes. The unit typically pre-treats the feedstock using washing and / or adsorbents to reduce P from 10-20 ppm to 1-2 ppm, but even at 1-2 ppm, protective materials are required.
[0005] Therefore, refiners processing renewable energy, whether using only renewable energy as feedstock or a blend of renewable energy and fossil fuels as feedstock, i.e. co-processing, have consistently expressed the need for better protective materials, particularly P-traps, to prevent pressure drop and deactivation of their bulk catalysts. It is therefore critical to reduce or, if possible, remove impurities, particularly phosphorus-containing species, before reaching the bulk catalyst.
[0006] The "guard bed" concept for catalytic processes is known. For example, it is known from U.S. Pat. No. 5,879,642. An upstream catalyst bed is used as a guard catalyst bed to remove a large portion of impurities from the hydrocarbon feed stream to extend the life of one or more catalyst beds located below (downstream) the catalyst guard bed.
[0007] US 9,447,334 (US 2011 / 138680) discloses a process for converting feeds derived from renewable sources using feed pretreatment, wherein upstream of the hydrotreatment step, an intensive pretreatment step for eliminating tramp elements such as phosphorus that are insoluble under the hydrotreatment conditions is carried out. This step comprises the use of an adsorbent free of catalytic material (free of catalytic metals) having a high surface area (e.g. 140 m 2 / g) and a high total pore volume (e.g. 1.2 ml / g).
[0008] US 2004 / 077737 discloses a catalyst for Fischer-Tropsch synthesis, comprising 3-35 wt% of cobalt supported on alumina, the alumina support having a diameter of less than 50 m 2 / g surface area and / or at least 10% alpha-alumina. Cobalt (Co) is appropriately combined with a metal promoter Re or Pt. In particular, when Co is promoted by Re or Pt, the content of Co in the catalyst is 5wt% or more. When only Co is used in the catalyst, its content is 12wt% or more.
[0009] US 4,510,092 discloses a method for 2 / g, a micropore volume of less than 0.1 ml / g and a macropore volume of less than 0.6 ml / g, preferably less than 0.3 ml / g. The micropore volume refers to the pores with a size of less than about The total volume of pores with a size greater than about The total volume of the pores. The nickel content is very high, 1-25%.
[0010] US 4,587,012 discloses a process for upgrading a hydrocarbon-containing stream to remove metallic impurities such as nickel, vanadium and iron using a catalyst containing more than 80% alpha-alumina. The catalyst material has a pore volume (PV) of only about 500 ml / kg (0.5 ml / g) and no more than 10% of macropores, i.e. no more than 10% of the PV is composed of pores with a radius greater than (diameter greater than ) hole.
[0011] Conventional and commercially available guard bed materials for P capture are in the form of catalysts made from high pore volume gamma-alumina supports with low metal content to provide hydroprocessing activity.
[0012] Typically, the use of metals in guard materials, especially metals with hydroprocessing activity such as Mo or Ni, leads to undesirable coking, which can lead to plugging of the guard bed, resulting in an unsuitable pressure drop. High metal content or the promotion of too high an activity leads to coking around the catalyst due to lack of hydrogen and high temperatures due to the exotherm.
[0013] Despite recent advances in this area, there remains a need for improved materials, particularly porous materials for use in guard beds to remove impurities such as P, particularly with feedstocks containing significant amounts of renewable energy, including feedstocks with 100% renewable energy, i.e., 100% renewable feeds. Summary of the invention
[0014] An object of the present invention is to provide a material comprising one or more metals having hydroprocessing activity which is able to capture impurities (particularly P) in hydrocarbon feedstocks and which minimizes coking during operation.
[0015] Another object of the present invention is to provide a material having higher P permeability than conventional materials and thus having improved P capture.
[0016] Another object of the present invention is to provide a material with a high capacity for capturing impurities (particularly P) in feedstocks originating from renewable sources or a combination of renewable sources and fossil fuels.
[0017] The present invention solves these and other objects.
[0018] Thus, in a first aspect of the present invention is a porous material, particularly a porous material for removing one or more impurities from a feedstock, the porous material comprising alumina,
[0019] - the aluminum oxide comprises α-aluminum oxide,
[0020] - the porous material comprises one or more metals selected from Co, Mo, Ni, W and combinations thereof,
[0021] - The porous material has a thickness of 1-110 m 2 / g BET surface area,
[0022] in,
[0023] the porous material has a total pore volume of 0.50-0.80 ml / g, for example 0.50-0.750 ml / g, or 0.55-0.70 ml / g, or 0.60-0.7 ml / g (600-700 ml / kg), (as measured by mercury porosimetry),
[0024] and
[0025] The porous material has a pore size distribution (PSD) in which at least 30 vol%, such as at least 40 vol%, at least 50 vol%, or at least 60 vol% of the total pore volume has a radius ≥ (40nm) pores, suitably with a radius ≥ (50 nm) pores, e.g., with a radius of at most (500nm) pores.
[0026] In an embodiment according to the first aspect of the invention, at most 60 vol% of the total pore volume, for example at most 40 vol% of the total pore volume, is composed of pores with a radius smaller than Pores with a radius smaller than or less than pores.
[0027] Mercury porosimetry was performed according to ASTM D4284.
[0028] When the radius is equal to or greater than or equal to or greater than When the larger pores are used for P capture, the radius is smaller than The smaller pores can better utilize the one or more metals in the porous material to provide hydroprocessing activity. For example, the porous material can exhibit a broad peak of a unimodal pore system, or a broad peak of a bimodal or even trimodal pore system, wherein in particular, the smaller pores make it possible to increase the hydroprocessing activity of the porous material.
[0029] BET surface area is measured according to ASTM D4567-19, which is a single-point determination of surface area by the BET equation.
[0030] In an embodiment according to the first aspect of the present invention, the content of α-alumina is 50-100 wt%, such as 65-95 wt%, or 60-80 wt% (as determined by XRD).
[0031] In an embodiment according to the first aspect of the present invention, the alumina further comprises θ-alumina and optionally γ-alumina.
[0032] In an embodiment according to the first aspect of the present invention, the content of θ-alumina is 0-50 wt%, such as 35-45 wt%, or 30-40 wt% (as determined by XRD).
[0033] In an embodiment according to the first aspect of the present invention, the content of γ-alumina is 0-10wt%, such as 5wt% or less (such as 1wt%) (as determined by XRD). Therefore, in a specific embodiment, the content of γ-alumina is 0wt%, that is, the porous material does not contain γ-alumina.
[0034] In an embodiment according to the first aspect of the present invention, the content of the one or more metals is 0.25-20 wt%, such as 0.25-15 wt%, 0.25-10 wt% or 0.25-5 wt%.
[0035] Combinations of the above features are also included. Thus, in an embodiment according to the first aspect, the content of α-alumina is 50-100wt%, such as 65-95wt%; the content of θ-alumina is 0-50wt%, such as 35-45wt%, and the content of γ-alumina is 0-10wt%, such as 5wt% or less (such as 1wt%) (as determined by XRD), and the content of one or more metals is 0.25-20wt%, such as 0.25-15wt%, 0.25-10wt%, or 0.25-5wt%.
[0036] XRD (X-ray diffraction) was performed according to standard XRD analysis, where powder X-ray diffraction patterns were collected on an XPertPro instrument configured in Bragg-Brentano mode using CuKα radiation and Rietveld analysis using TOPAS software was used to quantify phase composition.
[0037] Without being bound by any theory, it is believed that the formation of α-alumina and optionally θ-alumina as the main alumina phase of the porous material results in a significantly reduced surface reactivity of the porous material to P substances compared to, for example, the main γ-alumina phase in conventional materials or catalysts. Therefore, the reactivity to P substances is also reduced, so that P is not only captured on the surface of the porous material. At the same time, the porous material showing an increased pore size allows better penetration of feeds, especially renewable feeds, and thus penetration of P substances. In addition, it is also found that the use of one or more metals with hydroprocessing activity shows significantly less coking on the porous material, again without being bound by any theory, which can be attributed to the metal (e.g., Mo) blocking the remaining acid sites, or to some low hydrogenation activity of the porous material when the metal is present.
[0038] In an embodiment according to the first aspect, the porous material further comprises a compound selected from aluminum borates such as Al5BO9, calcium aluminates, silicon aluminates and combinations thereof. These compounds may exist in a crystalline form.
[0039] In a particular embodiment, the sum of theta-, alpha-, and gamma-alumina and any optional compounds described above present in crystalline form, such as calcium aluminate, is 100 wt% (as determined by XRD).
[0040] In another specific embodiment, the porous material is free of said compounds.Thus, the sum of theta-, alpha- and gamma-alumina (as determined by XRD) is 100 wt%.
[0041] In the preparation of the porous material, a starting (precursor) material comprising alumina and particularly having a large amount of γ-alumina (e.g., 50 wt% or more (as measured by XRD)) is calcined in air at a temperature of 1050°C or higher (e.g., 1100°C or 1200°C or 1300°C or 1400°C) for 1-10 hours, e.g., 4, 6 or 8 hours; e.g., at 1100°C for 2 hours, thereby converting γ-alumina into α-alumina and θ-alumina. Other alumina precursors such as boehmite may also be used in the preparation, for example, as a binder.
[0042] During the material preparation process, i.e., adding additives such as boric acid (H3BO3), calcium-containing compounds such as calcium nitrate (Ca(NO3)2) or silicon dioxide (SiO2) to the starting materials, it is possible to better control the sintering and / or transformation of the alumina phase during calcination, in particular, thereby achieving a smoother and more robust transformation. This also allows for better control of the surface area and pore size. Therefore, the additives act as stabilizers during the preparation of the porous material.
[0043] When such additives are used, these are then present in the porous material in the form of, for example, SiO 2 and / or in the alumina in the form of, for example, aluminum borate, calcium aluminate or silicon aluminate.
[0044] In another embodiment, the starting material comprising alumina, such as an alumina support, is a material pre-calcined at a temperature of 450-850°C, preferably 450-750°C.
[0045] When the feed contacts the main downstream catalyst bed for hydroprocessing, the guard material has some (albeit very low) hydroprocessing activity to avoid coking and high exothermicity. The most reactive molecules in the feed are converted, thereby reducing the risk of excessive temperature rise that may cause gelling. Therefore, a trade-off is achieved by the present invention: no metal will cause the material to coke, and too much metal activity will cause coking and gelling due to excessive temperature rise. Low metal content, such as 15wt% Mo, 10wt% Mo, 5wt% Mo or lower, such as 3wt% Mo, 1wt% Mo or 0.5wt% Mo, appropriately within the corresponding ranges described below, seems to just balance these two deactivation effects. In addition, some preheating before the feed reaches the bulk catalyst is also achieved.
[0046] In an embodiment according to the first aspect, the one or more metals include Mo, and its content is 0.5-15wt%, for example 0.5-10wt%, or 0.5-5wt%, or 0.5-3wt%, for example 0.5-1.5wt% or 0.5-1wt% such as 0.7wt% or 0.9wt%, or 1-2wt%; and optionally also includes 0.1-5wt%, for example 0.1-3wt%, 0.1-1wt%, 0.1-0.5wt%, or 0.1-0.2wt% of at least one Ni, Co, and W. In another embodiment according to the first aspect, the one or more metals include Mo, and its content is 0.5-15wt%, for example 0.5-10wt%, or 0.5-5wt%, or 0.5-3wt%, for example 0.5-1.5wt% such as 0.7wt% or 0.9wt%, or 1-2wt%, and optionally also includes 0.05-0.5wt% Ni; in addition, optionally, the porous material does not contain one or more metals selected from Co, W, that is, the porous material does not contain Co and / or W.
[0047] In a particular embodiment, at least one or more metals are Mo. In another particular embodiment, one or more metals are Mo and Ni. Thus, the porous material does not contain one or more metals selected from Co, W. For example, the porous material may contain 0.5-1.5wt% Mo, such as 1wt% Mo and 0.1-0.2wt% Ni. Due to the low surface area of the porous material, the Mo loading (Mo content) is reduced, but the low metal content can be compensated, for example, by adding Ni as a promoter. In addition, despite the low surface area of the porous material of the present invention, a small amount of molybdenum, such as 0.5-3wt% Mo, such as about 1wt%, leads to significantly lower coke formation. When operating with 100% renewable raw materials, the use of molybdenum is particularly advantageous because P capture is significantly increased relative to when molybdenum is not present in the porous material. In addition, the presence of a small amount of nickel (e.g., 0.05-0.5wt% Ni, such as about 0.1wt% Ni) further reduces coke formation.
[0048] The present invention does not require the use of any metal to provide P capture, however, the addition of Mo has been demonstrated to significantly reduce coking and, in any case, also enables the desired effect of achieving an activity gradient in an apparatus comprising a porous material. Furthermore, while the addition of Co or Ni as a promoter may be desirable because it significantly increases activity, this may be truly detrimental to a downstream hydroprocessing stage comprising at least one hydroprocessing catalyst. More specifically, when processing renewable feedstocks, it may be very detrimental to hydroprocessing / hydrodeoxygenation (HDO) selectivity (yield loss). While it is expected that oxygen removal from renewable feedstocks in HDO is primarily performed by removal of HO, especially nickel contents above about 0.5 wt% result in undesirable decarboxylation, thereby reducing HDO selectivity.
[0049] Materials catalytically active in hydroprocessing / HDO typically include an active metal (a sulfided alkali metal such as nickel, cobalt, tungsten and / or molybdenum, but also possibly an elemental noble metal such as platinum and / or palladium) and a refractory support such as alumina, silica or titania, or a combination thereof.
[0050] Hydroprocessing conditions include temperatures in the range of 250-400°C, pressures in the range of 30-150 bar and liquid hourly space velocities (LHSV) in the range of 0.1-2, optionally coupled with intermediate cooling by quenching with cold hydrogen, feed or product.
[0051] In an embodiment according to the first aspect, the BET surface area is 1-70 m 2 / g, for example 1-60m 2 / g, or 1-30m 2 / g, for example 10-30m 2 / g, for example 15-25m 2 / g, or 1-28m2 / g, 5-28m 2 / g, 10-28m 2 / g, 15-28m 2 / g, 20-28m 2 / g, 20-25m 2 / g, 5-20m 2 / g, or a combination thereof. A specific embodiment is 3-15m 2 / g, for example 9-10m 2 / g; or 25-30m 2 / g, 40-45m 2 / g, or 50-55m 2 / g.
[0052] In an embodiment according to the first aspect, at least one metal is in the form of an oxide or a sulfide.
[0053] In an embodiment according to the first aspect, the porous material is an extruded or tableted particle, and its shape is selected from trilobal, quadrilobal, pentalobal, cylindrical, spherical, hollow (e.g., hollow ring or hollow cylinder) and combinations thereof. Figure 4 As shown, particles having a four-lobed shape are particularly advantageous because of the improved surface area / volume ratio.
[0054] In a second aspect, the present invention also includes a method for removing one or more impurities from a feedstock, the method comprising the step of contacting the feedstock with a guard bed, thereby providing a purified feedstock, the guard bed comprising a porous material according to any of the preceding embodiments.
[0055] In an embodiment according to the second aspect of the present invention, the one or more impurities are selected from vanadium-containing impurities, silicon-containing impurities, halide-containing impurities, iron-containing impurities, phosphorus-containing impurities and combinations thereof. Preferably, the one or more impurities are phosphorus (P)-containing impurities.
[0056] In an embodiment according to the second aspect of the invention, the process is carried out at an elevated temperature, for example 100-400°C, for example 250-350°C, optionally in the presence of a reducing agent such as hydrogen.
[0057] In an embodiment according to the second aspect of the present invention, the raw material is:
[0058] i) Renewable sources obtained from feedstocks of renewable origin, for example from plants, algae, animals, fish, refined vegetable oils, domestic waste, waste rich in plastics, industrial organic wastes such as tall oil or black liquor, or from feedstocks derived from one or more oxygenates taken from the group of triglycerides, fatty acids, resin acids, ketones, aldehydes or alcohols, wherein the oxygenates are derived from one or more of biological sources, gasification processes, pyrolysis processes, Fischer-Tropsch synthesis or methanol-based synthesis. The oxygenates may also be derived from other synthetic processes. Some of these feedstocks may contain aromatic compounds; in particular products from pyrolysis processes or from wastes such as frying oils. Any combination of the above feedstocks is also contemplated.
[0059] The raw materials can also be:
[0060] ii) feedstocks derived from fossil fuels, such as diesel, kerosene, naphtha, vacuum gas oil (VGO), waste lubricating oils or combinations thereof;
[0061] or
[0062] iii) a feedstock derived from a combination of a renewable source according to i) and a feedstock derived from a fossil fuel according to ii)
[0063] In the context of the present invention, the terms "renewable source" and "renewable feed" are used interchangeably.
[0064] In a specific embodiment, the portion of the feedstock derived from renewable sources is 5-60 wt%, such as 10 wt% or 50 wt%. In another specific embodiment, the portion of the feedstock derived from renewable sources is higher than 60 wt%, such as 70-90 wt%.
[0065] In an embodiment according to the second aspect of the invention, one or more impurities are phosphorus (P) impurities, and the feedstock contains 0.5-1000 ppm P. The content of P can vary significantly depending on the feedstock. For example, in an oil derived from oxygenates from a pyrolysis process (e.g., pyrolysis oil), P is 50-60 ppm; or in a feedstock derived from animals (particularly animal fat), P is 100-300 ppm (e.g., 200 ppm).
[0066] In an embodiment according to the second aspect of the invention, the purified feedstock is subsequently treated in a hydroprocessing stage in the presence of a hydrogenation catalyst. In a particular embodiment, the hydroprocessing stage is located directly downstream, optionally with heating / cooling in between. In another particular embodiment, the hydroprocessing catalyst preferably comprises at least one metal selected from Co, Mo, Ni, W and combinations thereof.
[0067] In a third aspect, the invention comprises a guard bed for use in a hydroprocessing system, the guard bed comprising a porous material according to the first aspect of the invention.
[0068] In a fourth aspect, the present invention includes a hydroprocessing system for hydroprocessing a feedstock, the hydroprocessing system comprising:
[0069] A guard bed comprising a porous material according to the first aspect of the invention; and
[0070] A hydroprocessing section is disposed downstream of the guard bed and includes at least one hydroprocessing catalyst.
[0071] In a fifth aspect, the present invention also comprises the use of the porous material according to the first aspect of the present invention as a phosphorus protectant in a hydroprocessing process.
[0072] In a sixth aspect, the porous material is metal-free, for example, the porous material does not include one or more metals selected from Co, Mo, Ni, W, and combinations thereof. The present invention does not require the use of any metals to provide P capture.
[0073] Therefore, there is also provided a porous material comprising aluminum oxide,
[0074] - the aluminum oxide comprises α-aluminum oxide,
[0075] - the porous material does not include one or more metals selected from Co, Mo, Ni, W and combinations thereof,
[0076] - The porous material has a thickness of 1-110 m 2 / g BET surface area,
[0077] in
[0078] the porous material has a total pore volume of 0.50-0.80 ml / g, such as 0.50-0.75 ml / g, or 0.55-0.70 ml / g, or 0.60-0.70 ml / g (as measured by mercury porosimetry),
[0079] and
[0080] The porous material has a pore size distribution (PSD) in which at least 30 vol%, such as at least 40 vol%, at least 50 vol%, or at least 60 vol% of the total pore volume has a radius ≥ The pores are suitably of radius ≥ Pores with a radius of at most pores.
[0081] Any embodiment according to the first aspect of the present invention can be used together with any embodiment according to the second, third, fourth, fifth and sixth aspects of the present invention, and vice versa. It should also be understood that the embodiments according to the first to fifth aspects relate to the use of one or more metals selected from Co, Mo, Ni, W and combinations thereof, and these embodiments are not used together with the sixth aspect of the present invention.
[0082] BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 The pore size distribution (PSD) (determined by mercury porosimetry) of the porous material according to the invention is shown.
[0084] Figure 2 The pore volume distribution and the total pore volume (determined by mercury porosimetry) of the porous material according to the invention are shown.
[0085] Figure 3 Shows the radius on the X-axis is greater than The volume percentage of pores.
[0086] Figure 4 SEM (Scanning Electron Microscope) pictures of P entrapment in samples according to the prior art (low P penetration) and according to the invention (deep P penetration) are shown. Detailed description
[0087] Example
[0088] The porous material according to the invention is packed together with a reference porous material (i.e. a conventional commercially available refined catalyst having mainly a γ-alumina support impregnated with 3 wt% of Mo) in separate compartments and contacted with a mixture of 50% renewable feed and 50% fossil feed and 100% renewable feed for a period of time (typically 8-12 months) under hydroprocessing conditions. Before the test, the samples are analyzed by XRD, for example to determine the alumina phase. At the end of the test, the samples are rinsed and extracted by xylene, dried in vacuum, and analyzed for metal / P capture (XRF, X-ray fluorescence analysis according to EN ISO 12677:2011), SEM, carbon and sulfur (C+S; LECO analysis, ASTM E1915-13) and BET surface area (ASTM D4567-19).
[0089] Alumina phases were determined using XRD. Powder X-ray diffraction patterns were collected on an XPert Pro instrument configured in Bragg-Brentano mode using CuKα radiation. Rietveld analysis was performed using TOPAS software and used to quantify phase composition.
[0090] To determine the total pore volume and pore size distribution, mercury porosimetry was performed according to ASTM D4284.
[0091] The porous material is prepared as follows: without adding an alumina material used as a catalyst carrier as an additive, including 50 wt % or more of γ-alumina, and calcined in air at a high temperature of 1100-1200° C. for 2-3 hours.
[0092] Figure 1 The PSD of the four samples used in the test is shown. Note that the X-axis is logarithmic. Sample 1 is a reference according to the prior art, i.e. the conventional commercially available refined catalyst described above having primarily a gamma-alumina support. Samples 2-4 are porous materials according to the present invention. It is observed that for the samples according to the present invention, the pore radius of most of the pores is and larger, or The formation of these macropores for P capture is attributed to the formation of α-alumina and optionally θ-alumina.
[0093] Lower than or below Smaller pores may be beneficial in promoting some hydroprocessing capabilities of the porous material. Thus, Samples 3-4 specifically provide small pores to accommodate small amounts of metal, such as about 1 wt% Mo.
[0094] It is very delicate to find a balance of porous materials that have high impurity capture capacity, especially P capture capacity, while being able to accommodate metals for hydroprocessing, but not promoting coking. Such large pores do not guarantee better protection. For example, Figure 1 Above to about The peaks in the pore region do not necessarily make the corresponding porous materials (Samples 2 to 4) more porous than similar porous materials (i.e., at least 30 vol% of the total pore volume is equal to or larger than the radius or radius equal to or greater than pores, and in No peak is shown in the pore region, or At the same time, simply making the porous material have a large number of micropores or less than about or below The ability of the porous material to act as a P protector can be impaired by micropores blocking access to larger pores, since it is generally desirable to provide a high surface area for metal deposition and thus catalytic hydroprocessing activity.
[0095] Figure 2 and Figure 3 The total pore volume (PV) and the corresponding pore distribution are shown. The porous materials corresponding to samples 2 to 4 according to the present invention show a total pore volume in the range of 0.50-0.80 ml / g, more specifically about 0.60 ml / g, wherein the pores with a radius greater than The pores of the sample 2 account for at least 30% of the total pore volume. For example, sample 2 is about 90 wt% α-alumina and about 10 wt% θ-alumina, showing a pore volume greater than The pores account for 99% of the total pore volume, while the reference sample 1 shows more than The pores account for only about 20% of the total pore volume.
[0096] Table 1 shows the content of alumina phase in the samples measured by XRD. No additives were used as stabilizers in the preparation, so no aluminum borate, calcium aluminate or silicon aluminate crystalline phases were detected.
[0097] Table 1
[0098]
[0099] Table 2 below shows the results of impurity capture, especially P and Fe, and coking (C wt%) of porous materials with feedstocks of 50% renewable origin and 100% renewable origin.
[0100] Samples run with 50% renewable sources showed up to 600% higher P capture than the reference (Sample 1). Samples run with 100% renewable sources showed up to 51% increase in phosphorus capture. It was also shown that if a small amount of Mo, e.g. about 1 wt% Mo, is present in the fresh porous material, coking is significantly reduced (see underlined values) compared to the corresponding samples without the metal (3', 4'). Surprisingly, despite the lower surface area of the samples of the invention, the addition of e.g. 0.9 wt% and 0.7 wt% Mo results in significantly lower coke formation.
[0101] Figure 4 SEM images of P penetration into a porous material with a quadrilobate shape in the form of a P map (brighter means more P) are shown for reference sample 1 (top) and sample 2 (bottom). For the reference sample, P was observed to be present only on the surface of the material, while in sample 2, a high level of P penetration occurred.
[0102] Table 2
[0103]
[0104] Other experiments were conducted with another 100 wt% renewable feedstock, and the content of alumina phase in the fresh porous material (Samples 5, 6, 7; see Table 3 below) was about 70 wt% α-alumina and 30 wt% θ-alumina (as measured by XRD) with a surface area of 25-40 m 2 / g. Sample 1' (reference sample) is a new reference sample tested together with samples 5-7. Sample 1' (reference sample) has 100 wt% γ-alumina and a surface area of about 150 m2 / g, and contains slightly more molybdenum (about 3.1wt%) than sample 1 (reference sample). Similarly, no additives were used as stabilizers in the preparation, so no aluminum borate, calcium aluminate or silicon aluminate crystalline phases were detected. Sample 5 does not contain molybdenum and nickel. Sample 6 contains about 1wt% molybdenum. Sample 7 contains about 1.2wt% molybdenum and an additional about 0.1wt% nickel, more specifically, 0.14wt% Ni. All fresh porous materials (samples 1-7) do not contain Co and / or W. The results of the samples are shown in Table 3.
[0105] Again, significant P capture is achieved. Despite the lower surface area of the inventive sample, the addition of about 1 wt% Mo leads to significantly lower coke formation. By further adding a small amount of Ni (about 0.1 wt%), coke formation is further reduced without significantly compromising P capture.
[0106] The use of molybdenum optionally together with nickel is particularly advantageous when operating with 100% renewable feedstocks, as P capture is significantly increased relative to samples without molybdenum.
[0107] Table 3
[0108]
[0109] * Sample 7 is a NiMo porous material containing 0.14 wt % nickel.
Claims
1. A method of removing one or more impurities from a feedstock, the method comprising the step of contacting the feedstock with a guard bed, thereby providing a purified feedstock, the guard bed comprising a porous material, wherein the porous material comprises alumina, - the alumina comprises α-alumina, and the content of the α-alumina is 48-100wt%; - the porous material contains 0.25-5 wt% Mo, - The porous material has a thickness of 1-110 m 2 / g BET surface area, in - the porous material has a total pore volume of 0.50-0.80 ml / g, measured by mercury porosimetry, and The porous material has a pore size distribution in which at least 30 vol% of the total pore volume has pores with a radius ≥ Porosity; The one or more impurities are selected from phosphorus-containing impurities. 2 . The method according to claim 1 , wherein the porous material further comprises 0.05-3 wt % of one or more metals selected from Co, Ni and W. 3 .
3. The method according to claim 2, wherein the porous material comprises 0.1-1 wt% of one or more metals selected from Co, Ni and W. The method according to claim 2 , wherein the porous material contains 0.05-0.5 wt % Ni.
5. The method according to claim 1 or 2, wherein the porous material comprises 0.5-1.5 wt% Mo.
6. The method according to claim 1 or 2, wherein at most 60 vol% of the total pore volume is composed of pores with a radius smaller than pores.
7. The method according to claim 1 or 2, wherein the content of α-alumina is 65-95 wt%.
8. The method of claim 1 or 2, wherein the aluminum oxide further comprises theta-aluminum oxide.
9. The method of claim 8, wherein the alumina further comprises gamma-alumina.
10. The method according to claim 1 or 2, wherein the porous material further comprises a compound selected from the group consisting of aluminum borate, calcium aluminate, silicon aluminate, and combinations thereof. The method according to claim 1 , wherein the porous material does not contain Co and / or W.
12. The method according to claim 1 or 2, wherein the BET surface area is 10-70 m 2 / g.
13. The method of claim 1 or 2, wherein the porous material is an extruded or tableted particle having a shape selected from the group consisting of trilobal, quadrilobal, pentalobal, cylindrical, spherical, hollow, and combinations thereof.
14. The method of claim 1, wherein the one or more impurities are further selected from vanadium-containing impurities, silicon-containing impurities, halide-containing impurities, and iron-containing impurities.
15. The method according to claim 1 or 2, wherein the method is carried out at a temperature of 100-400°C.
16. The method according to claim 1 or 2, wherein the method is carried out in the presence of a reducing agent, hydrogen.
17. The method according to claim 1 or 2, wherein the raw material is: i) a renewable source obtained from raw materials of renewable origin, wherein the raw materials of renewable origin are derived from plants, animals, domestic waste, or industrial organic waste; or ii) a feedstock derived from fossil fuels, wherein the feedstock derived from fossil fuels is selected from diesel, kerosene, naphtha, vacuum gas oil, waste lubricating oil, and combinations thereof; or iii) A feedstock derived from a combination of a renewable source according to i) and a feedstock derived from fossil fuels according to ii).
18. The process according to claim 17, wherein the portion of the feedstock originating from renewable sources is 5-60 wt%.
19. The method of claim 17, wherein the renewable source feedstock is derived from algae or fish.
20. The method of claim 17, wherein the industrial organic waste is tall oil or black liquor.
21. The method of claim 17, wherein the renewable source feedstock is derived from refined vegetable oil.
22. The process of claim 1 or 2, wherein the feedstock is of renewable origin and is derived from one or more oxygen-containing compounds.
23. The method of claim 22, wherein the oxygenate is derived from one or more of a biological source, a gasification process, a pyrolysis process, Fischer-Tropsch synthesis, and a methanol-based synthesis.
24. The method of claim 22, wherein the oxygen-containing compound is selected from one or more of triglycerides, fatty acids, ketones, aldehydes and alcohols.
25. The method of claim 22, wherein the oxygen-containing compound is a resin acid.
26. The method of claim 18, wherein the portion of the feedstock derived from renewable sources is 10 wt%.
27. The method of claim 18, wherein the portion of the feedstock derived from renewable sources is 50 wt%.
28. The method according to claim 1 or 2, wherein the feedstock contains 0.5-1000 ppm of P.
29. The process according to claim 1 or 2, wherein the purified feedstock is subsequently treated in a hydrotreating stage in the presence of a hydrotreating catalyst.
30. The method of claim 1 or 2, wherein the porous material has a total pore volume of 0.60-0.75 ml / g.
31. The method according to claim 1 or 2, wherein 40-60 vol% of the total pore volume is pores.
32. The method of claim 31, wherein 50 vol% to 60 vol% of the total pore volume is pores with a radius ≥ pores.
33. The method according to claim 1 or 2, wherein 30-60 vol% of the total pore volume is pores with a radius ≥ pores.
34. The method of claim 1 or 2, wherein 30-60 vol% of the total pore volume is pores with a radius of at most pores.
35. Use of a porous material as a phosphorus protectant in the method of claim 1; the method comprising the step of contacting a feedstock with a guard bed, thereby providing a purified feedstock, the guard bed comprising the porous material, wherein the porous material comprises alumina, - the alumina comprises α-alumina, and the content of the α-alumina is 48-100wt%; - the porous material contains 0.25-5 wt% Mo, - The porous material has a thickness of 1-110 m 2 / g BET surface area, in - the porous material has a total pore volume of 0.50-0.80 ml / g, measured by mercury porosimetry, and The porous material has a pore size distribution in which at least 30 vol% of the total pore volume has pores with a radius ≥ Porosity; The feedstock contains one or more impurities; and The one or more impurities are selected from phosphorus-containing impurities.
Citation Information
Patent Citations
Process for converting feeds derived from renewable sources with pre-treatment of feeds by hot dephosphatation
US20110138680A1
Continuous reduction of edible oils
US4510092A
Fixed bed reactor assembly having a guard catalyst bed
US5879642A
Process for converting feeds derived from renewable sources with pre-treatment of feeds by hot dephosphatation
US9447334B2
Removing arsenic and / or phosphorus from liquid of hydrocarbon material using nickel capturer
CN1113261A